PENGARUH MOTIVASI TERHADAP KEPUTUSAN PEMBELIAN PADA HELMI HENDRA MOTOR KABUPATEN MAJALENGKA DEALER RESMI HONDA - Tia Aprilia Susnita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
The purpose of the research is to find and collect data and information needed toobtain a clear picture of consumer motivation and its impact on purchasingdecisions at Helmi Hendra Motor District Majalengka Honda Authorized Dealer.The method used in this research is qualitative (descriptive) and quantitative(verification) methods. The unit of analysis in this study is consumers who buymotorbikes at Helmi Hendra Motor District Majalengka Honda AuthorizedDealer with a sample of 68 respondents. The statistical test used is the calculationof the Pearson correlation, regression analysis, the coefficient of determination,hypothesis testing, and also using manual calculations.The results showed that there was a positive and significant influence betweenconsumer motivation on purchasing decisions at Helmi Hendra Motor DistrictMajalengka Honda Authorized Dealer. Because t count> t table or 13.4187>1.66827. The correlation coefficient (r) = 0.8554, which means that therelationship between consumer motivation and purchasing decisions is verystrong. The regression equation is Y = 1.79 + 0.82X. From this equation it can beconcluded that the constant value of 1.79 states that, if there is no increase in thevalue of variable X, the purchase decision price is 1.73. The regression coefficientof 0.82 states that each addition (due to the + sign) of one score, the value ofconsumer motivation will increase the score by 0.82 times. So every 1 timeincrease in the score is predicted to result in an increase in purchasing decisionsof 0.82X. The coefficient of determination which shows the effect of consumermotivation (variable X) on the ups and downs of purchasing decisions (variableY) is 73.18%. While the remaining 26.82% is influenced by other factors that arenot discussed in this study